Vascular Imaging of Matrix Metalloproteinase Activity as an Informative Preclinical Biomarker of Drug-induced Vascular Injury. (July 2017) - Gonzalez, Raymond J.; Lin, Shu-An; Bednar, Bohumil; Connolly, Brett; LaFranco-Scheuch, Lisa; Mesfin, Gebre M.; Philip, Thomas; Patel, Shetal; Johnson, Timothy; Sistare, Frank D.; Glaab, Warren E.
Lack of biomarkers specific to and either predictive or diagnostic of drug-induced vascular injury (DIVI) continues to be a major obstacle during drug development. Biomarkers derived from physiologic responses to vessel injury, such as inflammation and vascular remodeling, could make good candidates; however, they characteristically lack specificity for vasculature. We evaluated whether vascular remodeling–associated protease activity, as well as changes to vessel permeability resulting from DIVI, could be visualized ex vivo in affected vessels, thereby allowing for visual monitoring of the pathology to address specificity. We found that visualization of matrix metalloproteinase activation accompanied by increased vascular leakage in the mesentery of rats treated with agents known to induce vascular injury correlated well with incidence and severity of histopathological findings and associated inflammation as well as with circulating levels of tissue inhibitors of metalloproteinase 1 and neutrophil gelatinase–associated lipocalin. The weight of evidence approach reported here shows promise as a composite DIVI preclinical tool by means of complementing noninvasive monitoring of circulating biomarkers of inflammation with direct imaging of affected vasculature and thus lending specificity to its interpretation. These findings are supportive of a potential strategy that relies on translational imaging tools in conjunction with circulating biomarker data for high-specificity monitoring of VI both preclinically and clinically.